Blame attributions and rape: effects of belief in a just world and relationship level - Strömwall, Leif A. (Legal and criminological psychology, 2013)
Purpose. The blaming of rape victims can cause secondary victimization. It is of importance to investigate factor that might lead to victim blaming. This study investigated the effect of belief in a just world (BJW), gender of participant, and level of relationship closeness between victim and perpetrator on attributions of both victim and perpetrator blame. Methods. In a between-subjects experiment, a community sample (N= 166) answered questions of victim blame and perpetrator blame after reading one of four scenarios, each depicting a different level of relationship between the victim and the perpetrator (strangers, acquaintances, dating, or married). Results. Overall, high levels of perpetrator blame and low levels of victim blame were found. Contrary to previous research, the victim of a stranger rape was blamed more than when the perpetrator was known to the victim. Furthermore, participants high on BJW attributed higher levels of victim blame and lower levels of perpetrator blame. Specifically, female participants high on BJW attributed most blame to a victim of stranger rape. Conclusions. In conclusion, BJW was a significant predictor of blame attributions, and relationship type is a variable that merits further research.